2001
DOI: 10.1046/j.1365-2427.2001.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems with the application of diatom‐total phosphorus transfer functions: examples from a shallow English lake

Abstract: 1. A diatom‐total phosphorus transfer function has been applied to a sedimentary diatom sequence from Groby Pool, a small shallow lake in Leicestershire, U.K. 2. Extensive aquatic plant records exist for Groby Pool dating back over two centuries. These records, in conjunction with selected aquatic pollen and herbarium diatom data, provide independent, qualitative evidence for the progression of eutrophication and its effects on aquatic plant communities and habitat structure. 3. Before 1800, Groby Pool was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 40 publications
2
85
0
Order By: Relevance
“…The wide TP-tolerance range of these taxa reduces their utility as indicator species of TP. Sayer (2001) found that these taxa were more sensitive to habitat availability than to phosphorus in shallow lakes. It is more likely, therefore, that the decrease in Fragilaria taxa in Mitrofanovskoe Lake is caused by habitat changes (e.g., change in water level) or interspecific competition.…”
Section: Biological Indicators: Mitrofanovskoe Lakementioning
confidence: 97%
“…The wide TP-tolerance range of these taxa reduces their utility as indicator species of TP. Sayer (2001) found that these taxa were more sensitive to habitat availability than to phosphorus in shallow lakes. It is more likely, therefore, that the decrease in Fragilaria taxa in Mitrofanovskoe Lake is caused by habitat changes (e.g., change in water level) or interspecific competition.…”
Section: Biological Indicators: Mitrofanovskoe Lakementioning
confidence: 97%
“…However, several studies have highlighted the shortcomings of the transfer function technique in certain situations, and this is particularly well documented for shallow lakes where non-planktonic taxa dominate the diatom assemblages. Problems include the influence of factors such as light, substrate, and top-down factors in addition to water chemistry on the distribution of these taxa and their wide tolerance to nutrient concentrations, making them poor indicators of lake trophic status (e.g., Anderson et al, 1993;Bennion, 1995;Bennion et al, 2001;Sayer, 2001;Juggins et al, 2013). Nonetheless, in the absence of other techniques for hindcasting nutrient concentrations, inference models are likely to remain a valuable part of the lake manager's toolkit (SaulnierTalbot, 2015).…”
Section: Cyclotella Radiosa Cyclostephanos Dubiusmentioning
confidence: 99%
“…Furthermore, one has to allow for a good deal of approximation in the models and fits, accepting that the model will interpolate between adjacent time points and the strength of the fitted trend at any point is dependent upon the pattern in the data both prior and subsequent to any particular time point of interest. Caution must also be exercised when interpreting changes seen in surface sediment samples (upper 0-1 cm) in terms of recovery as the reduced period of decomposition experienced by recently deposited diatoms can result in these being over-represented (Sayer, 2001). Varved sequences, offering an annual resolution, lend themselves particularly well to studies of degradation and recovery (e.g., Chandler Rowell et al, 2015).…”
Section: Degradation Vs Recovery Pathwaysmentioning
confidence: 99%
“…Transfer functions based on modern-day relationships between a proxy, such as the distribution of diatoms, and an environmental variable, such as aquatic P concentration, are common techniques used to produce quantitative estimates of past changes. However, care is needed to exclude or disentangle the effects of strongly correlating variables on the response function (115,143,144).…”
Section: Discussionmentioning
confidence: 99%